REGULATION AND RESPONSIBILITY OF CLOUD COMPUTING STORAGE SERVICE PROVIDER TOWARDS PERSONAL DATA LEAKAGE RELATED TO LAW NUMBER 19 YEAR 2016 ABOUT AMENDMENT TO LAW NUMBER 11 OF 2008 CONCERNING ELECTRONIC INFORMATION AND TRANSACTIONS - Arsjad, Jesline; Dewi Rosadi, Sinta; Ratna Permata, Rika (P3M, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2021)
The rapid development of information technology that provides advantage apparently has a negative impact on users, namely the possibility of leakage of personal data. Cloud Computing is one example of IT development that provides uploading and downloading storage files in a very simple way. However, there were many cases involving the platform in the case of data leakage. The objective of this research is to identify the regulation and how the cloud computing service providers are responsible for this. Cloud computing is implicitly regulated in the Indonesian law which require registration of reliability certificates to guarantee its security. A law theory presented by Prof. Dr. Mochtar Kusumaatmadja, SH, LL.M., who stated that the law is progressive is not in accordance with cloud computing regulations that have not been specifically regulated.